Severe Anemia in Non Suicide Self Injury as a Complication of Major Depression Disorder - Tris Mardi; Arina Widya Murni (Biomedical Journal of Indonesia, 2021)
Non suicide self injury (NSSI) is a rare case in adults. Non suicide self injury is an act of hurting himself such as cutting, burning, punching without intending to commit suicide. NSSI itself is a complication of major depression that is not treated properly from the onset of symptoms. Severe depression that lasts for a long time, can aggravate illnesses such as the appearance of symptoms of psychosis and have an impact on various complications such as NSSI and somatic complications that can reduce the patient's health condition. Reported a case of a 22 year old woman with severe anemia due to chronic bleeding. It is known that chronic bleeding in the patient is the result of habitual cutting, in which the patient slashes her left forearm. Cutting habitualis is part of the action of NSSI where the management must be holistic and sustainable, the management of patients consists of psychotherapy as starting from dialectical behavior therapy is a form of cognitive therapy that can help a person adapt to activities that can pass through distress. Psychodynamic therapy is to help someone form new habits that previously could cause pleasure to the patient. Psychotherapy accompanied by psychopharmaceuticals can accelerate improvement in patient.